Feasibility of Brachial Occlusion Technique for Beat-to-Beat Pulse Wave Analysis - Matera, Lukas; Sajgalik, Pavol; Fabian, Vratislav; Mikhailov, Yegor; Zemanek, David; Johnson, Bruce D (Sensors (Basel, Switzerland), 2022)
Czech physiologist Penaz tried to overcome limitations of invasive pulse-contour methods (PCM) in clinical applications by a non-invasive method (finger mounted BP cuff) for continuous arterial waveform detection and beat-to-beat analysis. This discovery resulted in significant interest in human physiology and non-invasive examination of hemodynamic parameters, however has limitations because of the distal BP recording using a volume-clamp method. Thus, we propose a validation of beat-to-beat signal analysis acquired by novel a brachial occlusion-cuff (suprasystolic) principle and signal obtained from Finapres during a forced expiratory effort against an obstructed airway (Valsalva maneuver). Twelve healthy adult subjects [2 females, age = (27.2 ± 5.1) years] were in the upright siting position, breathe through the mouthpiece (simultaneously acquisition by brachial blood pressure monitor and Finapres) and at a defined time were asked to generate positive mouth pressure for 20 s (Valsalva). For the purpose of signal analysis, we proposed parameter a “Occlusion Cuff Index” (OCCI). The assumption about similarities between measured signals (suprasystolic brachial pulse waves amplitudes and Finapres’s MAP) were proved by averaged Pearson’s correlation coefficient (r- = 0.60, p < 0.001). The averaged Pearson’s correlation coefficient for the comparative analysis of OCCI between methods was r- = 0.88, p < 0.001. The average percent change of OCCI during maneuver: 8% increase, 19% decrease and percent change of max/min ratio is 35%. The investigation of brachial pulse waves measured by novel brachial blood pressure monitor shows positive correlation with Finapres and the parameter OCCI shows promise as an index, which could describe changes during beat-to-beat cardiac cycles.
Keywords: mladý dospělý; krevní tlak; Adult; Young Adult; Fingers; ženské pohlaví; occlusion; měření krevního tlaku; Blood Pressure Determination; lidé; Pulse Wave Analysis; analýza pulzové vlny; Feasibility Studies; srdeční frekvence; pulse wave; Brachial Artery; dospělí; Humans; cuff; prsty ruky; Heart Rate; Female; arteria brachialis; Blood Pressure; studie proveditelnosti; non-invasive